Why Isn't There More Progress in Philosophy?1. (3rd November 2014) - Chalmers, David J.
Abstract: Is there progress in philosophy? A glass-half-full view is that there is some progress in philosophy. A glass-half-empty view is that there is not as much as we would like. I articulate a version of the glass-half-empty view, argue for it, and then address the crucial question of what explains it.